Transmission Efficiency Calculation of 2K-H Negative Differential Gear Train in Main Hoisting Reducer of Ladle Crane - Shi Wenjie; Yang Liqiang; Liu Shijun; Wang Yong; Huang Hongtao; Jiang Jing (Jixie chuandong)
For a long time,the theoretical derivation value of the transmission efficiency of 2K-H negative differential gear train is high,however,there is large power loss of hoisting reducer epicyclic gear train in practice.The theoretical analysis and practical application is combined to discuss various factors and their proportion that impact the actual transmission efficiency of 2K-H negative differential gear train in main hoisting reducer of ladle crane,aiming to make the calculated value is closer to actual value.